Evaluation of mobile games with playability heuristic evaluation system - Soomro, S. (Institute of Electrical and Electronics Engineers Inc., 2014)
Heuristics evaluation is proved to be an efficient and effective method for inspecting usability of application software and game. However, it is reported in literature that negative usability results may cause failure to the product. In large projects usability evaluation in time consuming and due to time constraints project may fail. There is a need of improving method of conducting heuristic evaluation. Therefore, a motivation is raised to improve the method of conducting heuristic evaluation by automation the process. An automated heuristics evaluation tool empower users to focus on inspecting more usability problems within time constraints and reduce manual efforts. In this study, a playability heuristic evaluation system (PHES) is designed and developed to automate the process of conducting heuristics evaluation for games. To ensure the functionality of this systems, several tests were conducted. The results of this study advocates that with the help of playability heuristic evaluation system (PHES) more playability problems can be identified with in short time. Â© 2014 IEEE.